The Impact Of Source Credibility On Yemeni Male Consumers' Attitudes Toward Print Advertisement, Brand Attitudes And Purchase Intention Of Head Cover Product : The Moderating Role Of Brand Familiarity. - Abdulmajid, Methaq Ahmed (2009)
The understanding of consumers’ processes and activities that people engage in when searching for, selecting, purchasing, using, evaluating, and disposing of products and services to satisfy their needs and desires is crucial to guide